2021
DOI: 10.3390/ejihpe11030059
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related with Underperformance in Reading Proficiency, the Case of the Programme for International Student Assessment 2018

Abstract: Almost 217 million secondary school students (60% of the world’s adolescents) do not reach minimum levels in reading proficiency at the end of secondary school, according to objective 4.1 of the UN’s Sustainable Development Goals. Therefore, the early and efficient identification of this disadvantage and implementation of remedial strategies is critical for economies. In 2018, the Programme for International Student Assessment (PISA) assessed the reading skills of 15-year-old students in 80 countries and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…A group of studies have explored the links of student ICT use and reading literacy ( Hu et al, 2018 ; Gubbels et al, 2020 ; Vazquez-Lopez and Huerta-Manzanilla, 2021 ; Kong et al, 2022 ), and mixed results were found across studies. However, those studies failed to explain the mechanisms that resulted in the ambiguous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of studies have explored the links of student ICT use and reading literacy ( Hu et al, 2018 ; Gubbels et al, 2020 ; Vazquez-Lopez and Huerta-Manzanilla, 2021 ; Kong et al, 2022 ), and mixed results were found across studies. However, those studies failed to explain the mechanisms that resulted in the ambiguous findings.…”
Section: Discussionmentioning
confidence: 99%
“… Hu et al (2018) found that student ICT academic use negatively correlated with their reading literacy, while ICT entertainment use positively correlated with reading literacy. Regarding the relationship between ICT use for schoolwork both at home and school, mainly negative effects were found based on the analysis of PISA data in the large majority of countries ( Biagi and Loi, 2013 ; Petko et al, 2017 ; Hu et al, 2018 ; Vazquez-Lopez and Huerta-Manzanilla, 2021 ) with only a few countries or samples showing positive or null effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main research on the motivation generated by ICT in adolescents is related to education, especially in how the use of ICT in students, at home and at school, influences the performance of reading comprehension [5,45,46], mathematics [47,48] and science [47][48][49][50]. In these three domains or areas of knowledge, there are differences in academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing ICT use and its variables in this period is important, as it provides a clearer picture of the effects on motivation and academic performance in this student body [49]. Such research can create an early warning system that can identify students at risk of not developing adequate reading literacy in the future [45]. In this regard, there are studies linking the easy availability and autonomy of ICT with negative reading achievement, especially at home [5,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation